PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MATERI SISTEM TATA SURYA UNTUK SISWA SEKOLAH DASAR - Vera Yunita; Mahmud Alpusari; Eddy Noviana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Android-based learning media is an application that can be accessed and stored on a smartphone by the android operating system. Android can be made by the software aid, one of them is Smart App Creator. Hence, this article discusses the development of android-based learning media for sixth-grade elementary school students. The research is Research and Development with the 4D model. The validation obtained from the validator indicates an average score of 93.75% in the "Very Valid" category. The validator assessment of the teaching material expert indicates an average score of 86.81% in the "Very Valid" category. Assessment of research products in limited try-out uses the practicality of teachers and students. The average score result of teacher practicality is 91.06% with the very practical category. Subsequently, the acquisition result of students’ practicality indicates an average score of 87.09% in a very practical category. Based on this developmental research, android- based learning media on solar system material is very feasible to use for learning. Learning media is required to be optimized and utilized by teachers while the learning process and also implemented in other learning subjects.